Intervention to Improve Assertive Behavior in The Educational World: A Literature Review - Pahmiah, Pahmiah; Hasanati, Nida; Salsabila (Kirana Publisher (KNPub), 2024)
This study aims to explore the role of assertive behavior in educational contexts and to identify effective interventions to improve assertive behavior skills among students. Assertive behavior is defined as the ability to express thoughts, feelings, and needs in a clear and direct manner, while respecting others. In an academic context, this skill contributes to better academic achievement, more effective stress management, and positive interpersonal relationships. This study used a systematic review of the literature indexed in Scopus, PubMed, and Google Scholar databases from 2019 to 2024. The results of the review indicate that assertiveness training-based interventions, psychoeducational programs, and supportive environment-based approaches can significantly improve assertive behavior among students. This study concludes that the development of assertiveness skills should be an integral part of the educational curriculum with the aim of equipping students with the necessary skills to face the challenges of academic and professional life in the future